Media Motion Graphic Empat Pilar Gizi Seimbang Meningkatkan Pengetahuan Dan Sikap Ibu Balita - Agus Hendra Al Rahmad; Najwa Shavira (JURNAL RISET GIZI, 2024)
ABSTRACTBackground: Nutritional status is a major global health issue that frequently leads to the deaths of children under five years old. According to the World Health Organization (WHO), malnutrition accounts for 45% of deaths in this age group. In Indonesia, one key factor contributing to high rates of malnutrition among children under five is insufficient maternal knowledge. Enhancing maternal understanding of nutrition can be achieved through nutrition education, with Motion Graphics being one effective educational media.Research Objective: To assess the impact of Motion Graphic media education on the four pillars of balanced nutrition regarding the knowledge and attitudes of mothers with toddlers in Cot Gadong Village, Jeumpa District, Bireuen RegencyMethods: This study uses the Research and Development method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Primary and secondary data are collected, and they are subsequently put through editing, coding, scoring, processing, and cleaning steps. Both quantitative and qualitative data were acquired. Utilizing SPSS software for data analysis, the T-Dependent test with a 95% confidence level (Î± = 0.05) was included.Results: The average scores from the tests are as follows: 85.51% from the material expert, 85.96% from the media expert, and 93.33% from the language expert. The average knowledge level before education was 41.57, which increased to 83.33 after education. Similarly, the average attitude score rose from 40.20 before education to 87.23 after education. Statistical analysis shows p values of 0.000 for both knowledge and attitude.Conclusion: The creation of Motion Graphic media on the four pillars of balanced nutrition can enhance both the knowledge and attitudes of mothers with toddlers in Cot Gadong Village, Jeumpa District, Bireuen Regency.